A Batalla dos Xéneros= Gender Battle. - Aliaga, Juan Vicente; Jones, Amelia; Lebovici, Elisabeth; Olveira, Manuel; Pollock, Griselda; Rosa, Maria Laura (Santiago de Compostela : CGAC (Centro Galego de Arte Contemporanea) Santiago de Compostela, 2007)
Abramovic, Marina ; Akerman, Chantal ; Antin, Eleanor ; Balcells, Eugènia ; Bemberg, Maria Luisa ; Benglis, Lynda ; Berksoy, Semiha ; Berwick Street Film Collective ; Birnbaum, Dara ; Bourgeois, Louise ; Chicago, Judy ; Tee, Corinne ; Cosey Fanni Tutti ; Cottingham, Laura ; Edelson, Mary Beth ; Eulàlia ; Ferrer, Esther ; Fosso, Samuel ; Frazier, Susan ; Hodgett, Vicki ; Weltsch, Robin ; Geiger, Anna Bella ; Hammer, Barbara ; Harrison, Margaret ; Hidalgo, Juan ; Ivekovic, Sanja ; Journiac, Michel ; Keane, Tina ; Kelly, Mary ; Klauke, Jürgen ; Kubota, Shigeko ; Lacy, Suzanne ; Labowitz, Leslie ; Leppe, Carlos ; Lublin, Léa ; Lüthi, Urs ; Maiolino, Anna Maria ; Mayer, Monica ; Mendieta, Ana ; Messager, Annette ; Miralles, Fina ; Molinier, Pierre ; Pane, Gina ; Partum, Ewa ; Pazos, Carlos ; Piper, Adrian ; Potter, Sally ; Ringgold, Faith ; Rosenbach, Ulrike ; Rosler, Martha ; Schneemann, Carolee ; Sherman, Cindy ; Sjoo, Monica ; Spence, Jo ; Spero, Nancy ; Export, Valie ; Weibel, Peter ; Wilding, Faith ; Wilke, Hannah ; Yalter, Nil
Engels
Spaans
Exhibition. Gender Battle. Santiago de Compostela. CGAC (Centro Galego de Arte Contemporanea) Santiago de Compostela. 13.09.2007 - 09.12.2007
boek